Expenditure and financial burden for common cancers in China: a hospital-based multicentre cross-sectional study. (October 2016) - Huang, Hui-Yao; Shi, Ju-Fang; Guo, Lan-Wei; Zhu, Xin-Yu; Wang, Le; Liao, Xian-Zhen; Liu, Guo-Xiang; Bai, Ya-Na; Mao, A-Yan; Ren, Jian-Song; Sun, Xiao-Jie; Zhang, Kai; et al.
Abstract: Background: Comprehensive health economic evaluation, a key component of the Cancer Screening Program in Urban China (CanSPUC), was expected to support government policy-making on screening initiatives for common cancers (lung, breast, colorectal, oesophageal, liver, and stomach cancer) in urban China. Estimation of expenditure for cancer diagnosis and treatment from a societal perspective was an essential component. The aim of this study was to estimate direct medical and non-medical expenditure and to discern the resultant financial burden. Methods: A multicentre cross-sectional survey of patients with target cancers or precancerous lesions was conducted in 37 tertiary hospitals in 13 provinces across China, from 2012 to 2014. Each patient was interviewed with a structured questionnaire for sociodemographic, clinical, and expenditure information. Expenditure data was converted to 2014 values and presented as US$. Expenditure and financial burden were quantified as a whole and by subgroups. Findings: Of the included 14 594 patients with cancer (mean age 56·7 years, 58% male), annual household income was $8607. Mean expenditure per patient was $9739 (95% CI 9612–9866), and non-medical expenditure accounted for 9·3%. Expenditure per patient with colorectal, oesophageal, lung, stomach, liver or breast cancer was $10 978 (10 636–11 321), $10 506 (10 199–10 813), $9970 (9664–10 276), $9891 (9606–10 176), $8668 (8358–8977) and $8532 (8234–8831), respectively. Expenditure increased from stage I to stage IV for colorectal, stomach, and breast cancer (p<0·0001). Out-of-pocket expenditure of newly diagnosed cancer (2 months before and 10 months after diagnosis) per cancer patient was $4947 (4875–5020), accounting for 57·5% of annual household income, presenting 77·6% of families with an unmanageable financial burden. Apart from cancer site and stage, hospital type, education, occupation, insurance type, and previous years' household income were also significant predictors of expenditure (F=247·9, 56·3, 29·7, 12·8, and 28·7, respectively; all p<0·0001) as well as self-reported financial burden (χ 2 =130·4, 495·1, 1112·2, 1009·4, and 1848·2, respectively; all p<0·0001). In addition, for the included 1532 precancerous patients, mean expenditure was $3221 (3055–3387), a third of expenditure for patients with cancer. Interpretation: Expenditure for diagnosis and treatment seemed catastrophic for patients with cancer in China, and non-medical expenditure was substantial. Expenditure and financial burden varied within subgroups, especially between patients with different degrees of lesions, suggesting that cancer screening might be cost-effective in China. Funding: National Health and Family Plan Committee of China.